2004
DOI: 10.1557/proc-831-e3.6
|View full text |Cite
|
Sign up to set email alerts
|

The composition dependence of the optical properties of InN-rich InGaN grown by MBE

Abstract: Study of the relationship between the composition and optical energies of In x Ga 1-x N has generated much interest and intrigue over the last decade and beyond. In this paper we describe data from In x Ga 1-x N epilayers covering the full range of composition (0 < x < 1), grown by both Metal-Organic Vapour Phase Epitaxy (MOVPE) and Molecular Beam Epitaxy (MBE). In particular we concentrate on a set of state-of-the-art InN rich MBE layers (0.6 < x < 1.0). Wavelength dispersive X-ray microanalysis is employed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The bimodal distribution of NN bonds and their weak dependence on composition is probably a universal property of pseudobinary alloys 22 : it has also been observed in GaAsP 23 , CdMnTe 24 We now attempt to reconcile the local structure results described above with what is already known about the optical properties of the examined samples 29,30,31,32 .…”
Section: Resultsmentioning
confidence: 80%
“…The bimodal distribution of NN bonds and their weak dependence on composition is probably a universal property of pseudobinary alloys 22 : it has also been observed in GaAsP 23 , CdMnTe 24 We now attempt to reconcile the local structure results described above with what is already known about the optical properties of the examined samples 29,30,31,32 .…”
Section: Resultsmentioning
confidence: 80%
“…This clearly links the local structure with the emission properties and solves one mystery of the field. The Stokes' shift between absorption and emission is largest for samples with an intermediate range of InN content, [12][13][14] indicating that the highest degree of exciton localization occurs for this most mixed composition. However, the results presented in this letter show that the In and Ga local structure is the same for In-rich MBE samples ͑x ജ 60% ͒ and for MOCVD InGaN sample with 40% of InN.…”
mentioning
confidence: 95%
“…[8][9][10][11][12] Luminescence spectroscopy showed that the peak emission energies of comparable MBE and MOCVD samples were somewhat different: the emission peak energies of MBE samples were lower than those of MOCVD samples of similar composition. 9,10 This fact suggests that the higher degree of indium aggregation in MBE samples, compared to MOCVD samples of the same average composition, produces higher local InN fractions in InN-rich regions, leading to lower emission energies.…”
mentioning
confidence: 99%
“…III–N alloys exhibit a nonlinear band gap variation with concentration, called “bowing”. , The bowing parameter ( b ) determines how far from linear the band gap dependence on alloy composition is. In the general case of a binary alloy α (1– x ) β x N, b is defined as the coefficient of the nonlinear term in the phenomenological expression E normalg ( x ) = x E normalg α N + ( 1 x ) E normalg β N b x ( 1 x ) where E g αN and E g βN are the band gaps for the pure α and β nitrides, respectively.…”
mentioning
confidence: 99%